2010
DOI: 10.1517/14656566.2010.506188
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the clinical efficacy of asenapine in schizophrenia

Abstract: Importance of the field-Asenapine is a new atypical antipsychotic medication with high affinity for D 2 and 5HT 2A receptors that has been approved by the FDA in adults for the acute treatment of schizophrenia in the United States. The purpose of this review is to describe the compound and examine whether it addresses some of the unmet clinical needs in treating schizophrenia.Areas covered in this review-The development of asenapine is described with attention to its chemistry, pharmacodynamic and pharmacokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…The choice of asenapine as a treatment modality in this patient was based on the fact that, like ziprasidone and aripiprazole, it is associated with lower rates of weight gain. However, there are theoretical reasons to believe that this drug may be useful in supersensitivity psychoses per se, because asenapine is a potent antagonist of serotonin 5-HT2A receptors [ 20 ], and 5-HT2A blockade may reduce the D2 receptor supersensitivity responsible for these patients' symptoms [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The choice of asenapine as a treatment modality in this patient was based on the fact that, like ziprasidone and aripiprazole, it is associated with lower rates of weight gain. However, there are theoretical reasons to believe that this drug may be useful in supersensitivity psychoses per se, because asenapine is a potent antagonist of serotonin 5-HT2A receptors [ 20 ], and 5-HT2A blockade may reduce the D2 receptor supersensitivity responsible for these patients' symptoms [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of this model for developing antipsychotic treatment in schizophrenia has been covered elsewhere (Geyer and Moghaddam, 2002). A recent example, however, is the new atypical antipsychotic asenapine, initially approved for schizophrenia and now also approved for treating mania in BD (Minassian and Young, 2010). Early studies indicated that asenapine reversed the dopaminergic‐induced hyperactivity model of schizophrenia, consistent with other antipsychotics (Ellenbroek, 1993; Moore et al ., 1997; Geyer and Ellenbroek, 2003; Sun et al ., 2009).…”
Section: Pharmacological Models Of Maniamentioning
confidence: 99%
“…In addition, potential negative and cognitive symptoms resulting from asenapine need to be more closely investigated. The correct interpretation of data derived from the short-term trials is not easy, and meta-analytical studies are required to better understand these controversial points [138].…”
Section: Most Relevant Advantages and Disadvantages In The Utilization mentioning
confidence: 99%